One-Pot Synthesis of α-Substituted Acrylates - Matziari, Magdalini; Xie, Yixin (SynOpen, 2018)
A simple and efficient synthetic method towards α-substituted acrylic esters has been developed using the Horner–Wadsworth–Emmons (HWE) reaction with HCHO after alkylation of phosphonoacetates in a one-pot reaction. This method allows the smooth introduction of various side-chains, such as natural amino acids and other biologically relevant substituents. The use of mild conditions, inexpensive reagents, short reaction times and simple work-up and purification steps provides an effective and general alternative to cumbersome multistep and low-yielding procedures described to date.
Keywords: acrylates; Horner–Wadsworth–Emmons reaction; amino-acid analogues; one-pot synthesis; β-amino acids